Use of spermatozoa from epididymus of slaughtered rams for in vitro fertilization of ovine oocytes - WANI, N A; WANI, G M (The Indian Journal of Animal Sciences, 2014)
The oocytes harvested from the ovaries obtained from a local slaughterhouse were matured in vitro. The oocytes reaching to metaphase II stage were 63.21 %. The spenflatozoa used in this study were obtained from the cauda epididymus of 2-3 testes collected from local abattoir. The washed samples were having 70-80% motility, rising up to about 90% after swimup treatment. Sperm motility was maintained throughout the capacitation period in all the 3 media. At the time of insemination above 80% of the spermatozoa exhibited progressive motility in all the 3 media. The oocyte penetration rates were 46.5, 53.4 and 54.5, respectively, for oocytes in TCM-199, Hams F10 and Hams F12 respectively, Gut of the oocytes incubated further only 7,4 and 5.7% cleaved. It can be concluded that the spermatozoa collected from the epididymus of dead/slaughtered rams can be used successfully for the in vitro fertilization of oocytes in sheep.